Modes of acquisition of health literacy skills in informal learning contexts - António Geraldo Manso Calha (SciELO, 2014)
In this article we try to analyze the learning processes of health literacy skills in informal contexts. We intend to broaden the understanding of the learning process beyond the formal contexts, thus contributing to the elucidation of health professionals on how individuals acquire and manage their knowledge in health matters. Given our goal, we use an analytic corpus constituted by one hundred autobiographical narratives written between 2006 and 2011, in educational contexts but with recognized potential for use in different scientific fields, including health. The results reveal the existence of three different types of modes of learning health literacy skills in informal context: : i) learning that takes place in action, in achieving daily tasks; ii) learning processes that result from problem solving; iii) learning that occurs in an unplanned manner, resulting from accidental circumstances and, in some cases, devoid of intentionality.